2008
DOI: 10.1111/j.1365-2451.2008.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the unpreservable: a lost world rediscovered at Christian Malford, UK

Abstract: The small village of Christian Malford, Wiltshire (UK) is known to palaeontologists the world over because of the chance discovery of an astonishing fossil bonanza in the mid‐nineteenth century. Pits in the Jurassic Oxford Clay yielded thousands of specimens of exquisitely preserved ammonites, fish and crustaceans, but became most famous for squid‐like cephalopods and belemnites (collectively termed coleoids) with fossilized soft‐parts. The precise location of the find has remained obscure, until now, and a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…Such an assertion has added significance as oxygen isotopes derived from belemnites are a widely used standard to determine Jurassic temperatures (Rosales et al 2004;Price and Page 2008;Wierzbowski, 2004;Wierzbowski et al 2009;Dera et al 2011;Alberti et al 2012;Mettam et al 2014). Preservation of original nacreous aragonite characterizes much of the diverse molluscan fauna (Duff 1975;Martill and Hudson 1991;Wilby et al 2008) which includes denizens of both benthonic (bivalves, gastropods) and nektonic realms (ammonites). Also present are belemnites preserving both the calcitic rostrum and aragonitic phragmocone, allowing direct comparison of the two polymorphs.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Such an assertion has added significance as oxygen isotopes derived from belemnites are a widely used standard to determine Jurassic temperatures (Rosales et al 2004;Price and Page 2008;Wierzbowski, 2004;Wierzbowski et al 2009;Dera et al 2011;Alberti et al 2012;Mettam et al 2014). Preservation of original nacreous aragonite characterizes much of the diverse molluscan fauna (Duff 1975;Martill and Hudson 1991;Wilby et al 2008) which includes denizens of both benthonic (bivalves, gastropods) and nektonic realms (ammonites). Also present are belemnites preserving both the calcitic rostrum and aragonitic phragmocone, allowing direct comparison of the two polymorphs.…”
Section: Introductionmentioning
confidence: 96%
“…Hence, there is a need to fully evaluate the potential for isotopic disequilibria between ambient waters and different polymorphs of biogenic carbonate (e.g., Lécuyer et al 2012). In this study, previously proposed interpretations are re-evaluated in light of new isotopic data derived from a suite of exceptionally well-preserved Callovian (Middle Jurassic) mollusks from the Christian Malford Lagerstätte (Wilby et al 2004(Wilby et al , 2008Tang 2002). The Oxford Clay biota has been the subject of extensive previous isotopic work (e.g., Hudson 1978;Anderson et al 1994;Mettam et al 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of the Christian Malford Lagerstätte, Wilby et al (2008) illustrate and describe a number of coleoids that were collected over 170 years ago during construction of the Great Western Railway. During a re-investigation of the site in 2007, the British Geological Survey drilled a number of short boreholes and one of these (Core 10) has been investigated at Plymouth University.…”
Section: Statolithsmentioning
confidence: 99%
“…In the Callovian mudstones associated with the Christian Malford Lagerstätte (Wilby et al, 2008), exceptionally large numbers of statoliths have been found in normally prepared (White Spirit method of Brasier, 1980) micropalaeontology residues. Statoliths, like the otoliths in teleost fishes, are aragonitic 'stones' found in the stato-acoustic organs (statocysts) of squid.…”
mentioning
confidence: 98%